2021
DOI: 10.1111/ijcp.14699
|View full text |Cite
|
Sign up to set email alerts
|

Is heart rate variability a risk factor for premature ejaculation?

Abstract: Premature ejaculation (PE) is defined as the occurrence of ejaculation one minute or less after vaginal penetration. 1 Prevalence of PE in men is high and this sexual dysfunction affects 20%-30% of men. Although the aetiology of PE is not yet known clearly, many causes such as age and ethnicity have been blamed in its aetiology. 2 PE can negatively affect a person's psychological and emotional health by causing sexual avoidance and lack of self-confidence.Ejaculation is a spinal reflex under cerebral control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In line with findings regarding the role of HIIT in achieving the balance between sympathetic and parasympathetic activity, 26,29 it is plausible that the underlying mechanism is such that HIIT improves the PE symptoms in men by improving the sympathovagal imbalance, at least in men with PE. 13,17 For the daily PE symptoms measurement of CHEES-E for sexual events, first, in the first 7 days, there was no significant difference observed in CHEES-E between the HIIT intervention group and control group regardless of participants' PE status. Interestingly, after 7 days of intervention, in men with PE, the HIIT intervention group showed fewer PE symptoms than the control group.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In line with findings regarding the role of HIIT in achieving the balance between sympathetic and parasympathetic activity, 26,29 it is plausible that the underlying mechanism is such that HIIT improves the PE symptoms in men by improving the sympathovagal imbalance, at least in men with PE. 13,17 For the daily PE symptoms measurement of CHEES-E for sexual events, first, in the first 7 days, there was no significant difference observed in CHEES-E between the HIIT intervention group and control group regardless of participants' PE status. Interestingly, after 7 days of intervention, in men with PE, the HIIT intervention group showed fewer PE symptoms than the control group.…”
Section: Discussionmentioning
confidence: 91%
“…Also, a recent study found that during a 24-h interval of heart-rate monitoring, men with PE have lower parasympathetic activity and higher sympathetic/parasympathetic ratio, an indicator of the sympa-thovagal imbalance in the autonomic nervous system, compared with a control group. 13 Finally, a sympathetic/parasympathetic ratio above 2.7 predicted PE with high sensitivity. 13 Therefore, we assumed that sympathovagal imbalance may explain at least some of the etiology of PE.…”
Section: Sympathovagal Imbalance Hypothesismentioning
confidence: 99%
See 3 more Smart Citations